AKOMODASI KOMUNIKASI ETNIS TIONGHOA DAN SUNDA DI SURYA KENCANA BOGOR - Aprilyanti Pratiwi; Regiant Fachturahman Nurlatif; M. Girindra Madanacaragni (Jurnal Pustaka Komunikasi, 2021)
The purpose of this study was to identify the communication accommodation process carried out by ethnic Chinese and Sundanese in Surya Kencana, Bogor. The theory used in this study is Howard Giles' Accommodation Communication Theory (CAT). The results showed that the Chinese ethnic Surya Kencana initially made communication accommodations due to compulsion. However, over time and the positive feedback given by the Sundanese Surya Kencana, the Chinese finally made communication accommodations naturally. In the process of communication accommodation, the two ethnics converged, diverged and over-accomodated. The convergence carried out by Chinese is to use Indonesian mixed with Sundanese when communicating with Sundanese. The convergence carried out by the Sundanese is addressing the Chinese with ethnic greetings, (ko ko and ci ci). The divergence made by the Chinese is to be proud if they are called according to their ethnic origin. Meanwhile, the divergence made by Sundanese is to use Sundanese in a larger portion when interacting with ethnic Chinese. The over-accommodation made by the Chinese ethnic group is saying the word Alhamdulillah when interacting with the Sundanese group so that it seems forced. The over-accommodation made by the Sundanese is to greet the Chinese with a greeting according to their ethnicity but not according to the age context, so it seems impolite.